Thermotectonic history of the Brazilian continental margin from apatite fission track data - ENGELMANN DE OLIVEIRA, Christie H.; JELINEK, Andréa R. (Pesquisas em Geociências, 2017)
The Brazilian continental margin shows geomorphological structures formed during several episodes of tectonic activity initiated in the Neoproterozoic. In order to establish a thermotectonic history model for the Brazilian continental margin, an integration and reinterpretation of the apatite fission track (AFT) data was performed. AFT ages range from ~385 to 10 Ma. The AFT data reveal that the continental margin was characterized by at least three thermal events post Brasiliano Cycle: Early Cretaceous, Late Cretaceous and Paleogene-Neogene. The events are related to the opening processes of the South Atlantic Ocean and to the rift and post-rift phases, with tectonic reactivations along to the margin. The Mantiqueira Province and the São Francisco Craton record the oldest events, from the Ordovician to the Permian, respectively, which affected the various parts in varying ways as evidence of the Famatinian and Gondwanide orogenies. A margem continental brasileira denota estruturas geomorfológicas moldadas durante vários episódios de atividade tectônica iniciados no Neoproterozoico. Com o objetivo de estabelecer um modelo de história termotectônica para a margem continental brasileira, foi realizada a integração e reinterpretação dos dados traços de fissão em apatita (TFA) disponíveis ao longo de toda a margem continental. As idades TFA variam de ~385-10 Ma. Os dados TFA revelam que a margem continental foi caracterizada por pelo menos três eventos térmicos após o Ciclo Brasiliano: Cretaceo Inferior, Cretaceo Superior e Paleógeno-Neógeno. Os eventos são relacionados aos processos de abertura do Oceano Atlântico Sul e às fases rifte e pós-rifte, com reativações tectônicas ao longo da margem. A Província Mantiqueira e o Cráton São Francisco registram os eventos mais antigos, desde o Ordoviciano e o Permiano, respectivamente, que afetaram de modo variado diferentes partes dessas províncias como reflexo das orogenias Famatiniana e Gondwanide.